The Pićević family: Hum - Dabar nobility in the XIV and XV centuries - Pekić Radmilo B. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2019)
The paper presents a prominent noble family (Pićević), who was settled in Dabar, Hum land, during the fourteenth and fifteenth centuries. Based on Dubrovnik sources, then found inscriptions on the stećak tombstones, some members of this distinguished family and their subjects were shown. Until the fall of the Ottoman rule in 1465, the Pićević family were governed by provincial lords Vojinović as a part of medieval Serbia, later by the Bosnian rulers, Sanković and Kosač. The estates of the Pićević landlords were located in the settlements of Dabar: Ljuti Do, Potkom, Klečak, and Trusina. The medieval monuments of stećak tombstones, under which some of the members of this distinguished medieval family were buried, are located in these settlements as evidenced by the preserved tombstones.